Synergetic Effect of Blended Alkylamines for Copper Complex Ink To Form Conductive Copper Films - Xu, Wen (Langmuir : the ACS journal of surfaces and colloids, 2017)
Cu(II) complex ink consisting of copper formate (Cuf) and a primary alkylamine could yield highly conductive copper films at low heating temperatures without a reducing atmosphere. A synergetic effect of the blended alkylamines on the formation of conductive films was observed. It was found that blending two types of amines with different alkyl chain lengths as ligands could improve the conductivity of copper films, compared with using one of these amines alone. The decomposition mechanism of the Cuf-amine complex and the role of amines with different alkyl chain lengths were investigated. It was found that the decrease in the decomposition temperature and the formation of copper films were attributed to the activating effect and capping effect of the amine, and these two effects were dependent on the alkyl chain length. The relative intensity of the dual effects determined the decomposition rate of the complex and the nucleation and growth of particles. The use of blended amines with different alkyl chain lengths as ligands could balance the two effects and lead to appropriate nucleation and growth rates, so that densely packed copper films with low resistivity could be obtained at low heating temperature in a short time. The Cuf-butylamine-octylamine (Cuf-butyl-octyl) ink with 1:1 molar ratio of the amines showed the best performance. The understanding of the synergetic effect could provide guidance to the design of copper complex inks to control the morphology of the films